Application of SYBR Green Real-Time Quantitative PCR and Conventional PCR for the Detection of Methicillin-Resistant Staphylococcus aureus in Blood Samples - Warawan Wongboot (Science Faculty of Chiang Mai University, 2019)
Bloodstream infection with methicillin-resistant Staphylococcus aureus (MRSA) is a serious cause of morbidity and mortality worldwide. It is, therefore, essential to differentiate MRSA and methicillin-sensitive S. aureus (MSSA) in blood samples as quick as possible. The aim of this study was to evaluate the developed conventional PCR and SYBR green real-time PCR assays with the disc diffusion method. For this purpose, 86 blood samples with 76 signal-positive and 10 signal-negative blood samples that were incubated in an automated blood culture system were examined for the presence of S. aureus-specific gene (nuc) and the methicillin resistant gene (mecA) using conventional PCR and SYBR green real-time PCR assays. After 6 h incubation, the spiked-blood samples showed that the sensitivity for detection of MSSA as nuc positive and mecA negative was 1 CFU/ml and that of MRSA as nuc and mecA positive was 10 CFU/ml by both the conventional and SYBR green real-time PCR. The diagnostic accuracy of both PCR-based assays compared between genotypic method (nuc and mecA) and phenotypic method (disc diffusion) was 100% sensitivity, 97.5% specificity, 92.0% positive predictive value (PPV) and 100% negative predictive value (NPV). The results of this study indicated that the developed conventional PCR and SYBR green real-time PCR assays are high sensitivity, specificity, accuracy and could be applied as an effective screening tool for the direct detection of MRSA and MSSA in blood samples.